PENINGKATAN KETERAMPILAN KONEKSI MATEMATIS DAN SELF EFFICACY SISWA BERBASIS VIDEO PENGGUNAAN EDPUZZLE - Devina Urfa Fitrianti; Dewi Surani; Ratu Milawati; Namiroh Namiroh (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2023)
This study aims to increase mathematical connections and self-efficacy in obtaining positive responses from students who use interactive learning videos. Quantitative method with quasi-experimental techniques for this study sample of 74 students. Research data collection techniques are observation, test instruments, questionnaires and documentation. The results of the t test obtained from the table, reject Ho if Sig.≤α 0.05 then, the value of Sig. <than 0.05 then Ho is rejected and Ha is accepted, therefore the results of the data from both classes are Sig. > than 0.05 then Ho is rejected and Ha is accepted because (t-start -14.81 and t-two start 2.026) the conclusion that can be said is that the increase in mathematical connection ability and self-efficacy in the experimental class is better than that in the control class. The use of edpuzzle as a reference source for active media in class, can be seen from the response to a greater increase in experiments, namely 26.31% and vice versa 17.78%.